2004
DOI: 10.1007/s00125-004-1354-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of sensory disorders in diabetic Sprague-Dawley rats by aldose reductase inhibition or treatment with ciliary neurotrophic factor

Abstract: Aims/hypothesis. Sensory neuropathy in diabetic patients frequently presents itself as progressive loss of thermal perception, while some patients describe concurrent spontaneous pain, allodynia or hyperalgesia. Diabetic rats develop thermal hypoalgesia and tactile allodynia by unknown mechanisms. We investigated whether sensory disorders in rats were related to glucose metabolism by aldose reductase. We also explored the therapeutic potential of exogenous neurotrophic factors. Methods. Behavioural assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
102
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 52 publications
12
102
0
1
Order By: Relevance
“…Here, the tail-flick response latency appeared decreased in rats with short-term STZ-induced diabetes, consistent with independent measurements of the paw-withdrawal time from noxious thermal stimuli, which, in contrast to the tail-flick test, included supraspinal sensory processing (23). Diabetic rats demonstrated reduced latencies of both responses, which is consistent with the presence of transient thermal hyperalgesia and is in line with our previous studies (13,30) and other reports (3,7,9). Both tail-flick and paw-withdrawal latencies were at least partially corrected by PARP inhibition, consistent with other findings (3,4,7) implicating oxidative-nitrosative stress as well as other mechanisms contributing to free radical and oxidant generation (e.g., increased aldose reductase [9] and protein kinase C [26] activities) to abnormal sensory responses to thermal noxious stimuli in diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, the tail-flick response latency appeared decreased in rats with short-term STZ-induced diabetes, consistent with independent measurements of the paw-withdrawal time from noxious thermal stimuli, which, in contrast to the tail-flick test, included supraspinal sensory processing (23). Diabetic rats demonstrated reduced latencies of both responses, which is consistent with the presence of transient thermal hyperalgesia and is in line with our previous studies (13,30) and other reports (3,7,9). Both tail-flick and paw-withdrawal latencies were at least partially corrected by PARP inhibition, consistent with other findings (3,4,7) implicating oxidative-nitrosative stress as well as other mechanisms contributing to free radical and oxidant generation (e.g., increased aldose reductase [9] and protein kinase C [26] activities) to abnormal sensory responses to thermal noxious stimuli in diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Similar phenomenon is observed in diabetic rats where the light touch (Ͻ15 g) of von Frey filaments or light stroking of the paw induces a withdrawal response from the stimulus (9,23,25). The mechanisms of tactile allodynia are not studied in detail.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our study showed that glucose metabolism by aldose reductase contributed to the etiology of thermal hypoalgesia, and aldose reductase inhibition also normalized thermal responses. This is concordant with Calcutt et al (38), who showed the efficiency of ARI to prevent thermal hypoalgesia in 8-week diabetic rats. Thus, we suggest that restoration of normal algesia in sorbinil-treated diabetic mice is caused by recovery of C-fiber terminals, allowing for pressure-induced vasodilation restoration.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous pharmacological studies in animal models have been performed to sort out the involvement of the key hyperglycemia-induced biochemical mechanisms in diabetesassociated changes in thermal nociception. Aldose reductase inhibitors (ARIs, Calcutt et al, 2004), antioxidants i.e., taurine (Li et al, 2005b), α-lipoic acid (Cameron et al, 2001a), the hydroxyl radical scavenger dimethylthiourea (Cameron et al, 2001b), as well as the protein kinase C inhibitor LY333531 (Cotter et al, 2002), the PARP inhibitor 1,5-isoqunolinediol and PARP inhibitor-containing combination therapies (Li et al, 2005a), have been found to prevent or correct thermal hyperalgesia in STZ-diabetic rats. Taurine prevented thermal hyperalgesia in ZDF rats (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%